Kultur Pendidikan Islam di Minoritas Muslim Inggris (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
Religious education is a private need, but when they reside in society where the facilities is not available, Muslim family try to fulfill the need in many ways. Therefore, this article would identify Muslim minority in England. In-depth interview and observation were conducted to collect data in early stage. The next step was focus group discussion on several schedules to verify data. This study shows that there are three forms on education that England Muslim enjoy to fulfill education for their family, they are state school, private school, and community school. This article shows that Muslim society of England enjoy opportunities to express their faith, include on educational services. Finally, this article also discusses the motivation of the educational establishment and their effort to maintain the religion base knowledge management.